Pengaruh Persepsi Kemudahan, Persepsi Kebermanfaatan, Dan Kualitas Informasi Terhadap Minat Masyarakat Dalam Menggunakan Layanan Pencegahan Bunuh Diri Berbasis Teknologi Informasi - Nurhasida, Wiwin; Khadafie, Muammar; Jaya, Ahmad Ariga (Evolusi : Jurnal Sains dan Manajemen, 2024)
This study aims to analyze perceived convenience, perceived usefulness, and information quality on public interest in using information technology-based suicide prevention services. This study uses quantitative methodology and uses a causality approach to analyze data. The research sample amounted to 100 respondents who were Mataram City residents who knew information about suicide prevention services at Mutiara Sukma Mental Hospital, NTB Province. The data were analyzed using the Partial Least Square (PLS) method which is included in the Structural Equation Modeling (SEM) analysis. The results showed that perceived convenience, perceived usefulness, and information quality had a positive and significant effect on public interest in using information technology-based suicide prevention services. Then the three variables are able to influence public interest in using information technology-based suicide prevention services simultaneously. The conclusion is that the higher the public's perception of the ease of use, the benefits obtained, and the quality of information provided by the service, the higher their interest in utilizing it. This indicates the importance of designing and providing services that are easily accessible, useful, and provide accurate and useful information to encourage the utilization of information technology-based suicide prevention services.